(untitled) (International Journal of Applied Research in Management and Economics, 2020)
This paper aims to investigate Fertial’s CSR communication, to comprehend whether it is a voluntary adoption or it is due to external stakeholders’ influence. Unlike many empirical researches that have been carried out to address the matter of voluntary CSR communication, we have focused our research on analyzing data collected from Fertial’s “house journal”, which is called “Fertial News”. We have adopted a qualitative data analysis method for this research, in order to analyze codes assigned from the last ten issues of Fertial News. The results of this study show that most of Fertial CSR communications are considered as feedback to external stakeholders’ influence, in comparison to the amount of social information voluntarily communicated by Fertial.